Análisis del impacto económico de la integración de sistemas fotovoltaicos en el sector industrial del Ecuador - Barrigas Álvarez, Javier Andrés (2024)
This project analyzes the technical, economic, and environmental feasibility of implementing photovoltaic (PV) systems in the industrial sector in Ecuador. It highlights the importance of key parameters for the sizing of these systems, such as solar radiation, location, orientation and inclination of the panels, and the efficiency of the components. These factors are essential to achieve efficient PV systems, given the high energy consumption in the industry. The study examines the regulatory framework in Ecuador, specifying that industrial systems must be approved by the local power distributor, which is responsible for installing bi-directional meters. Current regulations establish capacity limits for residential and industrial systems, as well as the possibility of accumulating surplus energy for up to 24 months. In the economic analysis, six case studies were evaluated, and in none of them was economic profitability achieved. Although in two of the cases the IRR was positive, the negative NPV showed that profits would be lower than expected, with an IRR lower than 8 % of the Ecuadorian bank interest rate, which reduces the financial viability of the project. In addition, the unit cost of electricity (LCOE) turned out to be high compared to international values. In conclusion, although PV systems represent a sustainable and environmentally beneficial source, the results show that they are not economically viable for the cases analyzed. Keywords: photovoltaic systems, industrial sector, VAN, TIR, LCOE, ROI.